2022
DOI: 10.3348/kjr.2021.0476
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Performance of Radiologists Using Artificial Intelligence-Based Detection Support Software for Mammography: A Multi-Reader Study

Abstract: Objective To evaluate whether artificial intelligence (AI) for detecting breast cancer on mammography can improve the performance and time efficiency of radiologists reading mammograms. Materials and Methods A commercial deep learning-based software for mammography was validated using external data collected from 200 patients, 100 each with and without breast cancer (40 with benign lesions and 60 without lesions) from one hospital. Ten readers, including five breast spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 33 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…The supplementary literature search identified 48 eligible studies ( Fig. 1 ) [ 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 ]. Table 6 shows the count of studies that addressed the four value elements provided by AI.…”
Section: Resultsmentioning
confidence: 99%
“…The supplementary literature search identified 48 eligible studies ( Fig. 1 ) [ 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 ]. Table 6 shows the count of studies that addressed the four value elements provided by AI.…”
Section: Resultsmentioning
confidence: 99%
“…For mammography, studies have shown conflicting results, with reading times not being significantly affected by the use of AI 16 or decreasing up to 22.3% when AI results are available 17 . In a study by Lee et al, reading times were affected by the experience levels of radiologists even with AI, as general radiologists showed longer reading times; breast radiologists did not show any change in reading times with AI use 8 . Interestingly, a study by Pacile et al reported results for mammography that were similar to the findings seen in this study 18 .…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies have demonstrated better diagnostic performance with AI when reprioritizing brain computed tomography (CT) for the detection of hemorrhage 6 , 7 . Integration of AI into mammography has been found to enhance the diagnostic performance of radiologists without increasing reading time 8 . A similar tendency was observed in the detection of bone fractures using radiographs 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity varies from 60%–90% and is significantly affected by breast density [ 1 2 ]. Recently, artificial intelligence-based computer-aided diagnosis (AI-CAD) has been increasingly integrated into mammography, displaying a diagnostic accuracy comparable to or even superior to that of radiologists, while significantly enhancing the diagnostic performance of radiologists [ 3 4 5 6 7 ].…”
Section: Introductionmentioning
confidence: 99%